Meningkatkan Pemahaman Siswa Tentang Bahaya Penyalahgunaan Narkoba melalui Layanan Informasi - Habibah, Primanita Aisiy Nur (Indonesian Journal of Guidance and Counseling: Theory and Application, 2017)
The purpose of this research to know is there any progress in understanding abaut the dangerous of drug abuse after given information. The research, which is used, is a research using one grup pre test pre test-post test design. Pre test and post test us understanding test about the dunger of drug abuse. Sampling techingue, which is use, is random sampling, for 32 students. Hyphothesis test through trial test with 5% significancy, the result is tcount = 30,115 dan ttable = 2,042 it shows Ha is accepted and Ho is declined. The result of the research are (1) before given information service has high presentage about 67,49% (2) after given information service has in creased with high category and average about 94,21% (3) student understanding about the danger of drug abuse can be increased through information service. That guidance and counseling teacher can use information service to increase the understanding of drug abuse as preventive action.